Implementing CDIO standarda into conference week (TPU experience (on the example of foreign language); 11th International Technology, Education and Development Conference (INTED2017), 6-8 March, 2017, Valencia, Spain - Daneykin (Daneikin) Yu. V. Yuri Viktorovich (2017, 2017)
Title screen